2011
DOI: 10.1371/journal.pone.0019953
|View full text |Cite
|
Sign up to set email alerts
|

PCR Master Mixes Harbour Murine DNA Sequences. Caveat Emptor!

Abstract: BackgroundXMRV is the most recently described retrovirus to be found in Man, firstly in patients with prostate cancer (PC) and secondly in 67% of patients with chronic fatigue syndrome (CFS) and 3.7% of controls. Both disease associations remain contentious. Indeed, a recent publication has concluded that “XMRV is unlikely to be a human pathogen”. Subsequently related but different polytropic MLV (pMLV) sequences were also reported from the blood of 86.5% of patients with CFS. and 6.8% of controls. Consequentl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
40
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 24 publications
3
40
1
Order By: Relevance
“…This DNA is detectable in some batches and can thus generate false positive results. The results of the present study did not support this conclusion; the reagents used were provided by several different manufacturers, including the manufacturer used by Tuke et al 28 , and no false positives were observed. It thus seems more likely that contamination of reagents, human blood or tissue samples with murine genomic DNA was restricted to only a few research laboratories, which would account for the divergence of results.…”
Section: Ethical Considerationscontrasting
confidence: 89%
See 1 more Smart Citation
“…This DNA is detectable in some batches and can thus generate false positive results. The results of the present study did not support this conclusion; the reagents used were provided by several different manufacturers, including the manufacturer used by Tuke et al 28 , and no false positives were observed. It thus seems more likely that contamination of reagents, human blood or tissue samples with murine genomic DNA was restricted to only a few research laboratories, which would account for the divergence of results.…”
Section: Ethical Considerationscontrasting
confidence: 89%
“…The most likely explanation for false positive results is contamination of commercial PCR reagents [12][13][14] . Additionally, Tuke et al 28 proposed that a specifi c Taq DNA polymerase may contain monoclonal mouse antibodies with varying quantities of murine DNA. This DNA is detectable in some batches and can thus generate false positive results.…”
Section: Ethical Considerationsmentioning
confidence: 99%
“…There is no credible hypothesis that could explain these observations in the absence of PCR contamination. It appears to be extremely difficult to do mouse-free PCR, and we note that other studies in which contamination has been demonstrated have also amplified a diverse range of MLVs (27,38). We propose that the detection of murine virus in human samples be more rigorously controlled using IAP PCR (26) to rule out murine DNA contamination and robust phylogenetic analysis to rule out random amplification of endogenous proviruses (12), which can exist at a high copy number in the genomes of mice or in cell lines that become infected with mouse viruses during routine experimentation.…”
mentioning
confidence: 84%
“…Proposed reasons to explain the conflicting data are unknown but may be: technical differences, lack of standardized XMRV PCR assays, assay sensitivity, contamination by and cross-reactivity of XMRV PCR assays with closely related endogenous MLVs such as trace quantities of mouse genomic DNA found in reagents and samples (Hue et al, 2010;Oakes et al, 2010;Robinson et al, 2010;Sato et al, 2010;Knox, Carrigan et al, 2011;Tuke et al, 2011), differences in the geographical distribution of XMRV, sequence differences among XMRV genomes (Silverman et al, 2010;Singh et al, 2010;Knox et al, 2011) and factors related to the population genetic factors (Switzer et al, 2011).…”
Section: Introductionmentioning
confidence: 99%